Maintaining Sustainable Tourism through Management of Carbon Gas Emissions concerning Green Growth 2050 Bali Roadmap - Dewantara, Made Handijaya; Gaud, Christian Enriquez (Universitas Pendidikan Indonesia, 2022)
ABSTRACTThis study will provide insight in managing the carbon gas emission that Bali tourism development could raise. It will be related to the Green Growth Roadmap, released by the Provincial Government of Bali. Through an in-depth interview and desk research study, followed by a qualitative descriptive analysis, some strategies could be found that could be a way for the government to execute the carbon gas emission policy. We suggest an intensive collaboration between government and industry by setting a progressive target to reduce greenhouse gas emissions and determining a specific number. This article also suggests a mechanism by establishing a periodic report and assistance to anticipate gas emissions. Our research also found that promoting education and explaining the benefits of measuring and reducing greenhouse gas emissions. Conducting a research center dedicated to research and communication to help the business sector reduce emissions, including information in technology, facilitated by the academician. Last, creating an integrated certified system called